Clinical and Imaging Progression in the PARS Cohort: Long‐Term Follow‐up. Issue 9 (13th July 2020) - Siderowf, Andrew; Jennings, Danna; Stern, Matthew; Seibyl, John; Eberly, Shirley; Oakes, David; Marek, Kenneth; ,
Abstract: Background and Objectives: The PARS (Parkinson Associated Risk Syndrome) study was designed to test whether screening for hyposmia followed by dopamine transporter imaging can identify risk for conversion to clinical PD, and to evaluate progression markers during the prodromal period. Methods: Subjects with hyposmia completed annual clinical evaluations and biennial [ 123 I]ß‐CIT single‐photon emission computed tomography scans. Subjects were categorized as normal (>80% age‐expected tracer uptake; n = 134), indeterminate (>65–80%; n = 30), and dopamine transporter deficit (≤65%; n = 21) by their baseline scan, and survival analysis was used to compare risk of conversion to motor PD. Progressing to a scan with a dopamine transporter deficit was assessed for those subjects with either normal or indeterminate baseline imaging. Results: Over a mean of 6.3 [standard deviation: 2.2] years of follow‐up, 67% (n = 14) of dopamine transporter deficit subjects, 20% (n = 6) of dopamine transporter indeterminate subjects, and 4% (n = 6) of dopamine transporter normal subjects converted to a PD diagnosis ( P < 0.0001). Among subjects without dopamine transporter deficit at baseline, a reduction to ≤65% age‐expected uptake occurred in 12 of 30 (40%) with indeterminate dopamine transporter and 7 of 134 (5%) with no dopamine transporter DAT deficit ( P < 0.0001). Imaging conversion during follow‐up was associated with subsequent clinical conversion (hazard ratio: 9.6; P = 0.0157). Discussion and Conclusions: Long‐term follow‐up of the PARS cohort demonstrated a high rate of conversion to clinical PD in subjects who either had abnormal dopamine transporter imaging at baseline or developed abnormal imaging during follow‐up. These data extend the earlier PARS findings and present new results showing the sequence of incident imaging deficit, imaging progression, and clinical changes that occur in prodromal PD. © 2020 International Parkinson and Movement Disorder Society